Design Sociology Analysis in LA Bold Billboard Advertisements - Bekti, Pritha Fitria Natasha; Luqman, Ria Fathya; Prianingsih, Adua Angelita (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This study aims to analyze the design of the LA Bold billboard advertisement, released in 2025, as a form of social practice. This research uses a descriptive qualitative method with a sociology of design approach. Data are analyzed through key visual elements, including composition, color, typography, slogan, and visual representation. The results show that the LA Bold billboard represents a construction of masculinity, courage, and a modern lifestyle that targets young middle class urban men. Furthermore, the findings show that the design operates not only as a promotional media but also as a cultural product that shaped by social structures, particularly class stratification and consumer culture such as the upper,middle and lower classes. This design also reflects the complex relationship between consumer culture, the economic power of the cigarette industry, political regulations, and societal values that have evolved over time. Thus, design acts as a social intermediary that influences the perspectives and behavior of society. In conclusion, LA Bold’s billboard design functions as a social intermediary that both reflects and constructs social identity and meaning. The impact of this research underscores the role of visual design in shaping public perception and behavior, as well as the contribution to understanding design as part of broader sociocultural and economic practices.